Gender features of speech behavior in the main varieties of the English language - Kozokboeva , Dilfuzakhon (The Lingua Spectrum, 2025)
The article examines the use of English dismembered questions in the speech of British and American women and men. The practice of oral and written communication shows that this type of interrogative sentences in the speech of women and men constitutes a significant part (especially in the American variant).